The Use of Spiritual Emotional Freedom Technique (SEFT) Therapy as a Coping Strategy for Student Victims of Domestic Violence - Pramudya, Faizatul (Indonesian Scientific Publication, 2024)
This opinion article aims to provide recommendations regarding coping strategies that are suitable for female students who have experienced domestic violence. The coping strategy offered is Spiritual Emotional Freedom Technique (SEFT). SEFT therapy is a therapy that combines the body's energy system and spiritual therapy with the tapping method at several body points. Domestic violence is a form of violence that is rampant in Indonesia. Victims of domestic violence can be identified through their age, education and profession. If identified from the educational aspect, one of these victims is a female student. College students were chosen because as women who play the role of children in the family have the opportunity to become victims of domestic violence. SEFT therapy is recommended to overcome when these psychological impacts arise. From several literature studies conducted regarding the effectiveness of SEFT Therapy, it can be seen that this therapy is the right recommendation for female students who have experienced domestic violence.